Strategies for the Strengthening of Gastronomic Tourism in the Pastaza Canton, Ecuador - Fernández-Sánchez, Lineth (2016)
In the last decade worldwide social recognition to the local cuisine of indigenous peoples has achieved increasing levels, for their great contribution to the competitive value of tourism, becoming in many cases major player in the discovery of new sensory pleasures and experiences culinary. The study makes a diagnosis of restaurants registered as tourism, using the technique of direct and participatory observation with four instruments called checklists, which prior to were validated application using the DELPHI and ANOCHI methods, this for the processes of culinary development and food service sub-process of providing the service and cuisine and à la carte menu considered key activity. The results demonstrate the strengths and weaknesses exist, analyzed through the SWOT matrix of cross impacts that placed the object of study in quadrant III adaptive or reorientation. So, eight strategies consisting of 15 shares and 12 activities to improve service quality satisfy customers and respond to state policies in force were determined.